TWO CROFTON FORMULAS IN THE THREE-DIMENSIONAL SPACE - Aramyan, Rafik H.; Aramyan, Elen R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2024)
In this article, two Crofton-type integral formulas in the three-dimensional Euclidean space are obtained using integral geometry methods.